Estimation of the energy recovery potential of biogas from UASB reactors in the state of Rio Grande do Sul - Dilélio, Heron Vasconcellos (2025)
The increase in sewage collection and treatment rates in Rio Grande do Sul (RS) should be guided by environmentally and economically sustainable practices. Anaerobic digestion, through UASB reactors, thus becomes potentially attractive because it allows, in addition to sewage treatment, the generation and collection of biogas - a biofuel with a high methane percentage. Therefore, the present work has investigated the scope of UASB reactors’ operation in Rio Grande do Sul, identifying that 76.5% of its Sewage Treatment Plants (STPs) use anaerobic technology, with 1/3 having UASB reactors. Using self-monitoring data from the sectioned STPs and through the Chemical Oxygen Demand (COD) conversion methodology adapted from Lobato, Chernicharo, and Souza (2012) – incorporating a methane solubility fluctuation factor to better estimate losses in the liquid phase –, the energy potential of biogas generation in the state was estimated in three different scenarios. The results demonstrate that Rio Grande do Sul has low potential in this field due to the large number of small STPs, sewage with low COD concentration, and high methane losses in the liquid phase. Future individualized studies that address the financial viability are necessary, encompassing the perspective of less noble uses of biogas in order to provide additional revenue to the state's STPs.